Design of Improved Stream Cipher Algorithms for GSM Communication - Nur Hafiza Zakaria (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc.)--Faculty of Science and Technology, Universiti Sains Islam Malaysia, 2012